Outcomes Following Extrahepatic and Intraportal Pancreatic Islet Transplantation: A Comparative Cohort Study. Issue 11 (30th May 2022) - Verhoeff, Kevin; Marfil-Garza, Braulio A.; Sandha, Gurpal; Cooper, David; Dajani, Khaled; Bigam, David L.; Anderson, Blaire; Kin, Tatsuya; Lam, Anna; O'Gorman, Doug; Senior, Peter A.; Ricordi, Camillo; et al.
Abstract : Background: Preliminary studies show promise for extrahepatic islet transplantation (ITx). However, clinical comparisons with intraportal ITx outcomes remain limited. Methods: This single-center cohort study evaluates patients receiving extrahepatic or intraportal ITx between 1999 and 2018. Primary outcome was stimulated C-peptide level. Secondary outcomes were fasting plasma glucose, BETA-2 scores, and fasting C-peptide level. Multivariable logistic modeling evaluated factors independently associated with a composite variable of early graft failure and primary nonfunction within 60 d of ITx. Results: Of 264 patients, 9 (3.5%) received extrahepatic ITx (gastric submucosal = 2, subcutaneous = 3, omental = 4). Group demographics were similar at baseline (age, body mass index, diabetes duration, and glycemic control). At 1–3 mo post–first infusion, patients receiving extrahepatic ITx had significantly lower stimulated C-peptide (0.05 nmol/L versus 1.2 nmol/L, P < 0.001), higher fasting plasma glucose (9.3 mmol/L versus 7.3 mmol/L, P < 0.001), and lower BETA-2 scores (0 versus 11.6, P < 0.001) and SUITO indices (1.5 versus 39.6, P < 0.001) compared with those receiving intraportal ITx. Subjects receiving extrahepatic grafts failed to produce median C-peptide ≥0.2 nmol/L within the first 60 d after transplant. Subsequent intraportal infusion following extrahepatic transplants achieved equivalent outcomes compared with patients receiving intraportal transplant alone. Extrahepatic ITx was independently associated with early graft failure/primary non-function (odds ratio 1.709, confidence interval 73.8-39 616.0, P < 0.001), whereas no other factors were independently predictive. Conclusions: Using current techniques, intraportal islet infusion remains the gold standard for clinical ITx, with superior engraftment, graft function, and glycemic outcomes compared with extrahepatic transplantation of human islets. Abstract :